Distribution and Conservation Status of Sacred Groves (SGs) in Garo Hills, Meghalaya - Mohanta, R. K.; Bhardwaj, A. K.; Adhikari, B. S.; Mathur, P. K. (Indian Forester, 2009)
On a global scale, the existing Sacred Groves (SGs) follow ancestral worship and focus on conservation in forest patches. SGs are distributed over a wide ecosystem and help in conservation of rare and endemic species. Well preserved SGs are store houses of biological, ecological, medicinal, Ethno-cultural and religious values. During November 2006 to February 2007 we have documented 56 SGs in Garo Hills Area, among them 27 SGs in Garo Conservation Area (GCA). Thirteen SGs were randomly selected for detailed survey for the assessment of floral and faunal diversity, ethno-cultural values and management status. A total 149 plant species representing 131 genera with 52 families were recorded through floristic survey. 25 species of ethno-medicinal value are being used by local communities for cure from different diseases. Besides, 7 mammal species (6 genera), 33 bird species (27 genera) were recorded. In Garo Hills, SGs are small in size and can act as staring point for any long term conservation of biodiversity. The communities have still their faith and traditions linked to these mini nuclei of rich biodiversity in the landscape. Therefore, any conservation program can begin from local communities by taking them into confidence and empowerment through capacity building and awareness.